The Epidemiological and Spatiotemporal Characteristics of the 2019 Novel Coronavirus Disease (COVID-19) in Libya - Daw, Mohamed A.; El-Bouzedi, Abdallah H.; Ahmed, Mohamed O. (Frontiers in Public Health, 2021)
COVID-19 is a global pandemic that affected all aspects of life. Studies on understanding the geographical and epidemiological characteristics become particularly important in controlling the spread of the pandemic. Such studies are lacking in Northern African countries particularly in Libya, which considered being, the second largest country in Africa with the longest coast facing Europe. The objectives of this study are to; determine the epidemiological parameters and spatiotemporal patterns of COVID-19 in this large country and outline the needed strategies to contain the spread and the consequences of the pandemic. This comprehensive study included all the confirmed cases of COVID-19 since its emergence in Libya, from early April 2020 until July 31th. The epidemiological characteristics of COVID-19 were analyzed and the spatial dynamic trends were explored. A region -based counts of weekly reported cases were used to characterize and quantify the spatial dynamics of COVID-19. A total 3695 of confirmed cases of OVID-19 were collected, 2515(68.1%) were males and 1180(31.9%) female with a male-to-female(M:F) ratio 2.1:1. Aged between 2 -78 years old. Older age patients infected with COVID-19 are at higher severity and mortality. A broad geographic variability and Spatiotemporal spread variation of the COVID-19 pandemic in Libya was observed. Indicating a higher significant increase of COVID-19 from the middle of July particularly in the West and Southern regions although it was consistently observed in Meddle and Southern regions. Evaluating the epidemiological data and the spatiotemporal dynamic trends of COVID-19 at early stages are particularly important in understanding the pandemic spread. These parameters are essential in designing effective prevention and control programs aimed at reducing the impact of COVID- 19 pandemic particularly in countries with limited resources.